Antibiotic resistance and plasmid profiling of Vibrio parahaemolyticus isolated from cockles (Anadara granosa) at Tanjung Karang, Kuala Selangor - Bilung, Lesley Maurice; Velnetti, Linang; Cheah, Yoke Kqueen; Radu, Son; Apun, Kasing; Lihan, Samuel; Vincent, Micky; Nishibuchi, Mitsuaki (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
A total of sixty V. parahaemolyticus strains isolated from local cockles (Anadara granosa) were investigated by their antibiotic resistance patterns and plasmid profiles. The isolates showed multiple resistances towards most of the antibiotics tested. All strains of V. parahaemolyticus isolated harbored 1-3 plasmids, with sizes ranging from 2.7 to 54 kb. All V. parahaemolyticus strains showed high multiple antibiotics in frequencies of 0.58 - 0.94 indicating that the strains were derived from high-risk sources. In addition, no particular plasmid profile was predictive of a particular pattern of antibiotic susceptibility. These findings are essential because of the suggested involvement of seafood especially shellfish and environment in transmission of this pathogen to human. Thus, indicating that seafood may be a source of food- acquired antibiotic resistant bacteria to consumer.